An Endophytic Trichoderma Strain Promotes Growth of Its Hosts and Defends Against Pathogen Attack - Tseng, Yu-Heng; Rouina, Hamid; Groten, Karin; Rajani, Pijakala; Furch, Alexandra C. U.; Reichelt, Michael; Baldwin, Ian T.; Nataraja, Karaba N.; Uma Shaanker, Ramanan; Oelmüller, Ralf (Frontiers in Plant Science, 2020)
Plants host numerous endophytic microbes which promote plant performance, in particular under stress. A new endophytic fungus was isolated from the leaves of a deciduous wood tree Leucas aspera. Morphological inspection and multilocus phylogeny identified the fungus as a new Trichoderma strain. If applied to Arabidopsis thaliana and Nicotiana attenuata, it mainly colonizes their roots and strongly promotes initial growth of the plants on soil. The fungus grows on high NaCl or mannitol concentrations, and shows predatory capability on the pathogenic fungus Alternaria brassicicola. Colonized Arabidopsis plants tolerate higher salt stress and show lower A. brassicicola spread in roots and shoots, while arbuscular mycorrhiza formation in N. attenuata is not affected by the Trichoderma strain. These beneficial features of the novel Trichoderma strain are important prerequisites for agricultural applications.